Evaluation of the effect of cannabidiol administration with and without nonsteroidal anti-inflammatory drugs in dogs with mobility disorders: a prospective, double-blind, crossover, placebo-controlled study - Talsma, Bryce; Elam, Lindsay Hochman; McGrath, Stephanie; Zhou, Tianjian; Webb, Craig B.; Duerr, Felix Michael (Frontiers in Veterinary Science, 2024)
IntroductionWith rapidly growing interest in the use of cannabidiol (CBD) in the management of pain and other conditions, more information is needed on the safety and efficacy of this supplement, particularly its co-administration with commonly used pharmaceuticals such as non-steroidal anti-inflammatory drugs (NSAIDs). This study sought to assess the effect of CBD in dogs with mobility impairments, as well as evaluate the clinical tolerance of CBD used together with NSAIDs.Materials and methodsForty-two client-owned dogs with diagnosed mobility impairments were enrolled in this prospective, double-blind, crossover, placebo-controlled study. Baseline data were collected for 10–14 days followed by random allocation to either placebo or CBD oil for 45 days with a 30-day washout period in between. CBD was dosed at 5 mg/kg orally every 12 h with masked placebo administered at equal volume. Outcome measures included objective gait analysis, accelerometry, and clinical metrology instruments. CBD plasma levels and serum biochemistry were also collected along with hepatic ultrasound if warranted.ResultsThirty-eight dogs finished the study with thirty-nine included for at least partial analysis. Compared to baseline, dogs receiving CBD showed evidence of improved outcomes based on blinded veterinary assessments and accelerometer data. Compared to placebo, dogs receiving CBD showed some evidence of improved outcomes on CBPI, CSOM, and blinded veterinary assessments, but not for objective outcome measures. There was evidence of increased ALP when CBD was co-administered with NSAIDs compared to CBD administration alone. Additionally, there was evidence of ALT elevations with CBD and NSAID co-administration, but this elevation did not show evidence of an increase over CBD use alone.DiscussionThese results suggest a potential therapeutic benefit in the administration of CBD for the management of mobility impairments, but greater ALP elevations were seen when administered with NSAIDs. While the sample size of dogs that received further hepatic work-up for liver enzyme elevations is small, chosen diagnostics varied, and liver biopsies were not performed, there did not appear to be clinically apparent liver damage. Further research is needed to better understand the efficacy of CBD in a larger population of dogs and patient tolerance and safety when administered with NSAIDs or other medications long term.